The Use of Sarcasm as a Satirical Tool in The Dictator: A Pragmatic Analysis (2012) - Panggah Wahyu Bayu Aji; Abdur Rofik (Metaphor, 2025)
This study analyzes the use of sarcasm as a satirical tool in the film “The Dictator” (2012) starring Sacha Baron Cohen. This study aims to identify the types of sarcasm used in the film and how the audience responds to the sarcasm. The research method used is qualitative analysis using pragmatic and semantic theories to understand how sarcasm is used as an effective satirical tool. The results of the study indicate that there are four types of sarcasm used in the film, namely lexical sarcasm, “like”-prefixed sarcasm, illocutionary sarcasm, and propositional sarcasm. The audience’s response to the sarcasm varies, including off-record politeness responses, confrontational responses, and ignoring sarcasm. This study shows that sarcasm can be used as an effective satirical tool to criticize power and dominant ideologies in society in a humorous and ironic way. Thus, this study can contribute to the understanding of the role of sarcasm in communication and social criticism.